Transition Metal Dichalcogenides for the Application of Pollution Reduction: A Review - Zhang, Xixia; Teng, Sin Yong; Loy, Adrian Chun Minh; How, Bing Shen; Leong, Wei Dong; Tao, Xutang (Nanomaterials (Basel, Switzerland), 2020)
The material characteristics and properties of transition metal dichalcogenide (TMDCs) have gained research interest in various fields, such as electronics, catalytic, and energy storage. In particular, many researchers have been focusing on the applications of TMDCs in dealing with environmental pollution. TMDCs provide a unique opportunity to develop higher-value applications related to environmental matters. This work highlights the applications of TMDCs contributing to pollution reduction in (i) gas sensing technology, (ii) gas adsorption and removal, (iii) wastewater treatment, (iv) fuel cleaning, and (v) carbon dioxide valorization and conversion. Overall, the applications of TMDCs have successfully demonstrated the advantages of contributing to environmental conversation due to their special properties. The challenges and bottlenecks of implementing TMDCs in the actual industry are also highlighted. More efforts need to be devoted to overcoming the hurdles to maximize the potential of TMDCs implementation in the industry.
Keywords: layered materials; transition metal dichalcogenide (TMDCs) nanomaterials; catalysis; emission control; pollution reduction; gas cleaning; nanocatalysis